Perancangan, pembuatan dan pengujian Sensor Sudut Cerdas (Intelligent Angle Sensor) - Muljowidodo Muljowidodo; Muhammad Nur Muhadi (Mesin, 2001)
Angle sensor has been used in many systems demanding angle information of moving object. Angle sensor reported here has no damping as well as filtering system, therefore vibration information inherently in the construction of sensor will be included in the measured data. Algorithm in the intelligent control system will calculate the angle value separated from any vibration data, and the results have been compared to the ideal value where no vibration occurs during measurement.